Study of The Effectiveness of Integrating Adaptation and Mitigation Actions To The Impacts of Climate Change In Coastal Areas: A Case Study of Botanical Gardens Surabaya Mangroves - Dyan Prasetyaningtyas; Ipung Fitri Purwanti (International Journal of Science and Environment (IJSE), 2025)
Climate change has led to an increased risk of abrasion, tidal flooding, and ecosystem degradation in coastal areas, particularly in urban areas such as Surabaya. The Surabaya Mangrove Botanical Garden (KRMS) serves as an ecosystem-based conservation area that also plays a crucial role in climate change mitigation through carbon sequestration and protection against extreme climate impacts. This study aims to assess the effectiveness of integrating adaptation and mitigation actions in KRMS based on three main aspects: technical, social, and institutional. The research approach uses a combination of quantitative and qualitative methods, using the Analytic Hierarchy Process (AHP) method to assess expert perceptions and Structural Equation Modeling (SEM) to analyze community perceptions. Vegetation analysis was conducted using the Normalized Difference Vegetation Index (NDVI) for the period 2015–2025. The results show an increase in the NDVI value from 0.21 (2015) to 0.63 (2025), indicating successful vegetation rehabilitation and improved ecosystem quality. AHP shows that the social aspect has the highest weighting (0.3712), followed by the technical aspect (0.3228) and the institutional aspect (0.3059). SEM results show that institutional (β = 0.557; p < 0.001) and technical (β = 0.251; p = 0.0079) aspects significantly influence the effectiveness of integration, while social aspects are not statistically significant. This study concludes that the effectiveness of adaptation and mitigation integration in KRMS depends on the synergy between these aspects. Strengthening institutional governance, increasing community ecological literacy, and optimizing the function of mangrove vegetation as blue carbon are the keys to adaptive and sustainable coastal area management.